2016
DOI: 10.1186/s13054-016-1298-1
|View full text |Cite
|
Sign up to set email alerts
|

Enteral versus parenteral nutrition in critically ill patients: an updated systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundEnteral nutrition (EN) is recommended as the preferred route for early nutrition therapy in critically ill adults over parenteral nutrition (PN). A recent large randomized controlled trial (RCT) showed no outcome differences between the two routes. The objective of this systematic review was to evaluate the effect of the route of nutrition (EN versus PN) on clinical outcomes of critically ill patients.MethodsAn electronic search from 1980 to 2016 was performed identifying relevant RCTs. Individual tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
204
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(234 citation statements)
references
References 49 publications
(59 reference statements)
3
204
0
15
Order By: Relevance
“…PN is associated with nosocomial infection and prolonged intensive care length of stay, but not mortality (2,3). The most-updated nutrition support guideline recommends that EN should be started within 24 to 48 hours after admission, while PN can be withheld for seven days depending on the risk of malnutrition (4).…”
Section: Introductionmentioning
confidence: 99%
“…PN is associated with nosocomial infection and prolonged intensive care length of stay, but not mortality (2,3). The most-updated nutrition support guideline recommends that EN should be started within 24 to 48 hours after admission, while PN can be withheld for seven days depending on the risk of malnutrition (4).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, after the publications of the CALORIES [5] study showing no harm related to PN in ICU patients, unfounded biases regarding the detrimental effect of early PN must be reconsidered together with the amount of calories administered [1]. Elke et al [6], in a review of the literature, compared PN to EN when the calories administered were similar and could not find any difference in terms of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies comparing EN with PN in the era of "optimal calorie" intake have shown that early nutrition support is beneficial regardless of the route (10,11). Studies from 1983-2014 showed that PN was associated with increased infection complication only when patients in the PN arm received more calorie than those in the EN arm, but when calories were provided for EN or PN in similar amounts, the difference in infectious complications was no longer observed (12). This has been nicely shown again in the NUTRIREA-2 trial where PN was found not to be harmful when given in optimized amounts.…”
mentioning
confidence: 99%